Manajemen Digitalisasi Kurikulum Merdeka di SMP - Sa'id, Sukron; Hidayati, Dian; Suyatno, Suyatno; Sukirman, Sukirman (Universitas Muhammadiyah Surakarta, 2024)
This article explores the Management of Merdeka Curriculum Digitalization at the Junior High School (SMP) level as a response to the impact of the Covid-19 pandemic. The government and educational institutions are challenged to adapt to the new situation, including the development of online learning models. In this context, digital literacy is crucial, involving not only technical skills but also wise attitudes and behaviors towards digital information. The article highlights the importance of digital curriculum management to ensure education in line with the spirit of Merdeka Belajar. Challenges such as limited access to technology, teacher training, and the protection of student data privacy are addressed, with proposed solutions and implementation strategies. School principals and policymakers are expected to lead digital transformation in schools, emphasizing the importance of collaboration among schools, teachers, students, and parents. By understanding Merdeka Curriculum Digitalization Management comprehensively, it is expected to create an educational ecosystem that is adaptive, innovative, and responsive to technological developments.